Aflatoxin B1 contamination in papaya fruits (Carica papaya L.) during post harvest pathogenesis - BAGWAN, N.B. (Indian Phytopathology, 2011)
An investigation on post-harvest diseases of papaya fruits at Udgir fruit market showed association of nine fungi. These nine fungi were isolated from papaya fruits showing rotting symptoms that are displayed for sale in retail shops. The fungi isolated from decayed papaya fruits were: Gloeosporium papaya, Fusarium solani, F. moniliforme, Rhizopus stolonifer, R. nigricans, Botrydiplodia theobromae, Curvularia lunata, Aspergillus flavus, and A. niger. All these fungi were found to be highly pathogenic leading to rapid deterioration of papaya fruits. A detailed investigation was carried out only on Aspergillus flavus producing aflatoxin B1. Fifteen isolates of Aspergillus flavus obtained from decayed papaya fruits were screened for aflatoxin B1 production in naturally spoiled and artificially inoculated fruits. Nine isolates were found to produce aflatoxin B1 in naturally spoiled as well as in artificially inoculated fruits. Aflatoxin B1 produced by these isolates in naturally spoiled fruits ranged from 97.5 to 553.1Âµg/kg of fruit pulp, while aflatoxin B1 production by these nine toxigenic isolates in artificially inoculated fruits ranged from 37.3 to 613.1Âµg/ kg of fruit pulp. Results of this investigation lead to two important points: firstly, nine fungi found to be associated with post-harvest rots of papaya fruits and had many fold effects on fruits nutritional value; secondly the quantity of aflatoxin B1 produced by Aspergillus flavus isolates was very high, which is a great concern to the health of consumers.